The Influence of Social Support and Psychological Resilience on Santri’s Behavior - Hasanah, Uswatun; Mundiri, Akmal (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2024)
This study aims to elucidate the influence of social support and psychological resilience on student behavior. The research is motivated by the need to understand the factors influencing student behavior within the scope of education. Social support is an important factor that can affect the psychological and social development of students, while psychological resilience reflects students' ability to cope with challenges and stress in everyday life. The research approach employed is quantitative with a correlational design. Data for this study were obtained through questionnaires and analyzed using multiple linear regression techniques. ased on the findings of this research, it was found that: 1) There is a positive influence of social support on psychological resilience, as evidenced by the value of 0.187, which is smaller than 0.698. 2) There is a positive influence of social support on student behavior, which is 0.329, smaller than 0.698. 3) There is a positive influence of psychological resilience on student behavior, amounting to 0.195, smaller than 0.684. 4) There is a simultaneous influence of social support and psychological resilience on student behavior, amounting to 0.367, smaller than 0.604. This indicates that social support and psychological resilience play an important role in shaping student behavior. The higher the social support and psychological resilience obtained by students, the higher the positive influence on student behavior. The findings of this research are expected to provide new insights into the importance of social support and psychological resilience in shaping student behavior.